PENGEMBANGAN KECERDASAN EMOSI ANAK USIA DINI KELOMPOK BERMAIN CIKAL GEMILANG (5-6 TAHUN) DENGAN METODE QIROATI - LESTARI, PUJI (IKIP Siliwangi, 2018)
AbstractEmotional development is an important of developed from adult around the child. One of them is from teacher in they school. Emotional quetiont recently has first ranking in the live of life and to get a job. So, it’s natural that teacher was participate to development emotional ability from childhood. One of the method is by using Qiroati method. A method to read and write about Al-Qurán’, which is the aim is just not to development spiritual ability, but to development emotional ability too. The research is doing by Classroom Action Research (Penelitian Tindakan Kelas), a research which have the quality reflective by doing certain action in order to correct how to increasing the practice of learning in the class according to professional. The technique of collect the data are observation, interview and documentation. The subject research are 10 chilhood about 5-6 years, with 6 girls and 4 boys. The result from this research is by using 2 cycle, which from 2 cycles indicating that the emotional ability of childhood can rise by Qiroati method.analysis data gained from pracycle and pascacycle.